Learn to create with Disaster Mitigation Digital Comics Project : Meningkatkan Kreativitas dan Hasil Belajar dengan Model Project Based Learning di SMAN 1 Kepanjen - Meliana Sasi Madyaningtyas; Widya Ayu Rarassita Dewi; Yuristya Dyah Indriani; Alfyananda Kurnia Putra; Eva Febriyanti (Jurnal Penelitian dan Pendidikan IPS, 2022)
Abstract The purpose of this study is to develop a project-based learning model to support increased creativity and student learning outcomes in teaching and learning activities. Project-based learning (PjBL) is an effective learning method because it emphasizes contextual learning through complex activities. The focus of learning activities lies in concepts that involve students in problem solving investigations and tasks activities to develop creativity, provide opportunities for students to work to test their own knowledge, and achieve their goal of producing real products. The advantage is to develop communication and collaboration skills between students because through the activity of the learning model, students are able to unite opinions and respect each other's different opinions in achieving the main objectives of project implementation. The result of the product in the form of a comic from the creativity of a group of students. It is hoped that the application og the PjBL learning model will increase student creativity in working on the planned